Bibliometric analysis and short survey in CT scan image segmentation: identifying ischemic stroke lesion areas - Wahabou K. Taba Chabi; Sèmèvo Arnaud R. M. Ahouandjinou; Manhougbé Probus A. F. Kiki; Adoté François-Xavier Ametepe (Institute of Advanced Engineering and Science, 2025)
Ischemic stroke remains one of the leading causes of mortality and long-term disability worldwide. Accurate segmentation of brain lesions plays a crucial role in ensuring reliable diagnosis and effective treatment planning, both of which are essential for improving clinical outcomes. This paper presents a bibliometric analysis and a concise review of medical image segmentation techniques applied to ischemic stroke lesions, with a focus on tomographic imaging data. A total of 2,014 publications from the Scopus database (2013–2023) were analyzed. Sixty key studies were selected for in-depth examination: 59.9% were journal articles, 29.9% were conference proceedings, and 4.7% were conference reviews. The year 2023 marked the highest volume of publications, representing 17% of the total. The most active countries in this area of research are China, the United States, and India.